Temperature variability and its effect on seasonal yield of rice in Bangladesh: a long-term trend assessment - Md. Abdullah Al Mamun; Md. Abdur Rouf Sarkar; Mou Rani Sarker; Andrew M. McKenzie; Sheikh Arafat Islam Nihad; Md. Arafat Hossain; Akbar Hossain (Cogent Food & Agriculture)
Bangladesh, an agriculturally reliant and climate-vulnerable country, requires real-time quantification of climatic variables, such as temperature, to sustain food security. However, the effects of spatial and temporal temperature variations on rice productivity across seasons remain underexplored. Our study addresses this gap by analyzing temperature data from 35 meteorological stations (1970-2020) using parametric and nonparametric methods. The Mann-Kendall test revealed a pronounced increase in minimum temperatures compared to maximum temperatures, particularly during the monsoon season. K-means clustering identified four seasonal station clusters, revealing that rising minimum temperatures positively influenced Aus rice yields in seven regions, while temperatures above 35°C negatively affected yields, especially in northwest Bangladesh. Seasonal heat incidence highlighted that Aus rice experienced greater temperature stress compared to Aman and Boro. Wavelet coherence analysis confirmed that recent heat events significantly impacted Aus and Boro yields, with high-frequency temperature anomalies affecting Aus and Aman. Regression analysis attributed 11–47% of Aus, 4–70% of Aman, and 7–52% of Boro rice yield variations to temperature fluctuations. Despite localized disruptions, Bangladesh has sustained rice self-sufficiency through adoption of stress-tolerant varieties, mechanization, and improved practices. To ensure climate-resilient food security, targeted regional policy planning and implementation are imperative.